Hubungan Komitmen Organisasi Dan Intensi Turnover : Meta-Analisis - Annisa Nur Wahyuni (INSIGHT: JURNAL PEMIKIRAN DAN PENELITIAN PSIKOLOGI, 2019)
Turnover intention is. The purpose of this study was to conduct a meta-analysis survey related to organizational commitment relationship in generating turnover intention behavior through 15 studies covering both variables and sample criteria of employees. Based on the results of the analysis, the results obtained r = -0,307145, which can be concluded that organizational commitment has a correlation to turnover intention behavior. thinking of leaving the job, and that the intention to leave work correlates with the actual abandonment of the job (turnover). Then organizational commitment is expressed in a variety of ways. In addition to leaving the job (turnover) the employee can complain of widening, avoiding responsibility.